Determinación de la susceptibilidad a procesos de remoción en masa en el municipio de sogamoso,a partir del uso de análisis espacial (2022)
In order to obtain the susceptibility to mass removal processes in the municipality of Sogamoso at a scale of 1: 25,000, a sum of maps was made involving spatial thematic variables such as geological units, geomorphological units, slope of the terrain, curvature of the terrain, units of land cover, land use and delimitation of existing mass removal processes, where a bivariate statistical method (weight - evidence) is applied to determine the index of susceptibility to landslides, implementing the “Methodology Guide for the zoning of the threat due to mass movements on a scale of 1: 25,000 ”proposed by the Colombian Geological Survey in 2017. As a result, achieving a classification of susceptibility to mass removal processes in four corresponding categories with low 24%, medium 68%, high 6.9% and very high 1.1% of the total area of the municipality. Finding that urban developments should be projected towards the alluvial valley area, and industrial projects, linear projects or human settlement towards the mountainous area require geotechnical studies that include the stability of the slopes.